Diallyldimethylammonium Chloride (DADMAC) in Water Treated with Poly-Diallyldimethylammonium Chloride (PDADMAC) by Reversed-Phase Ion-Pair Chromatography—Electrospray Ionization Mass Spectrometry - Francesca Di Gaudio; Salvatore Barreca; Santino Orecchio (Separations, 2023)
Poly-diallyldimethylammonium (PDADMAC) chloride is a flocculant agent extensively used in water clarification treatments. Commercial polyelectrolyte formulations often contain residual monomer (DADMAC), reaction by-products and other reactants as contaminants that could potentially affect human health. In the present study, we optimized an analytical method based on reversed-phase ion-pair chromatography coupled with mass spectrometry for quantifying ultra-trace levels of DADMAC, without preliminary treatments, in drinking water distributed by the Palermo aqueduct. The method was validated in terms of accuracy (recovery between 80 to 120%), precision (RSD < 10%), linearity range (from 0.5 to 15 µg/L), limit of quantification and limit of detection (LOQ 0.42 µg/L and LOD 0.12 µg/L). DADMAC was detected in all analysed water samples and the concentration ranged from 1.2 to 3.8 µg/L whit a mean value of 1.7 µg/L. To the best of our knowledge, this paper represents the first study concerning DADMAC concentration in water samples collected in Italy and, in this context, this paper can be considered very interesting when comparing future data on DADMAC monitoring in water. Moreover, this is one of a few cases where DADMAC was found in drinking water.